SOURCES OF MANGANESE DEPOSITED AS OCEANIC FE-MN ORE - Bazilevskaya E.S. (My University, 2006)
The current concepts of two competing sources of manganese deposited as oceanic Fe-Mn ore are reviewed and assessed critically. A new solution of this problem proposed in this paper is a further development of fundamental works by N.M. Strakhov in the light of new facts and with allowance for geological, geochemical, and geohistorical data. It has been concluded that terrigenous material removed from land serves as a main source of manganese fixed in oceanic Fe-Mn ore. The history of sedimentation and nodule formation in the World Ocean lasted for more than two billion years. Manganese has been supplied to recent bottom sediments from both present-day and older sources. The closed geochemical cycle of Mn circulation in the ocean is intimately related to its circulation in the hydrosphere. Seawater is oversaturated with Mn and serves as its immediate source for ore deposition and elevated concentrations in bottom sediments affected by hydrothermal solutions or other manifestations of endogenic activity. Seawater is a repository for Mn, where this element is retained during global cataclysms, which have repeatedly occurred in geological history. © Pleiades Publishing, Inc. 2006.